Association of amygdala size with stress perception: Findings of a transversal study across the lifespan. (5th September 2022) - Caetano, Inês; Amorim, Liliana; Castanho, Teresa Costa; Coelho, Ana; Ferreira, Sónia; Portugal‐Nunes, Carlos; Soares, José Miguel; Gonçalves, Nuno; Sousa, Rui; Reis, Joana; Lima, Catarina; Marques, Paulo; et al.
Abstract: Daily routines are getting increasingly stressful. Interestingly, associations between stress perception and amygdala volume, a brain region implicated in emotional behaviour, have been observed in both younger and older adults. Life stress, on the other hand, has become pervasive and is no longer restricted to a specific age group or life stage. As a result, it is vital to consider stress as a continuum across the lifespan. In this study, we investigated the relationship between perceived stress and amygdala size in 272 healthy participants with a broad age range. Participants were submitted to a structural magnetic resonance imaging (MRI) to extract amygdala volume, and the Perceived Stress Scale (PSS) scores were used as the independent variable in volumetric regressions. We found that perceived stress is positively associated with the right amygdala volume throughout life. Abstract : Previous studies have shown associations between stress perception and amygdala volume in narrow age‐ranged cohorts. Life stress, on the other hand, has become pervasive and is no longer restricted to a specific age group or life stage. Herein, using a sizeable healthy cohort, we show that perceived stress is positively associated with the right amygdala volume across lifespan.